Knock-Down of GPR88 in the Dorsal Striatum Alters the Response of Medium Spiny Neurons to the Loss of Dopamine Input and L-3-4-Dyhydroxyphenylalanine - Ingallinesi, Manuela; Galet, Benjamin; Pegon, Jonathan; Faucon Biguet, Nicole; Do Thi, Anh; Millan, Mark J; Mannoury la Cour, Clotilde; Meloni, Rolando (Frontiers in Pharmacology, 2019)
The effects of L-3,4-Dihydroxyphenilanlanine (L-DOPA) treatment for replacing the dopamine (DA) loss in Parkinson’s disease (PD) progressively wear off and are hindered by the development of dyskinesia, prompting the search of new treatments. The orphan GPCR Gpr88 represents a potential new target, as it is highly and almost exclusively expressed in the projecting GABAergic medium spiny neurons of the striatum, is implicated in motor activity and is downregulated by 6-OHDA lesions, an effect that is reversed by L-DOPA. Thus, to evaluate Gpr88 as a potential target for the management of Parkinson’s disease and L-DOPA-induced dyskinesia (LID), we inactivated Gpr88 by lentiviral-mediated knock-down with a specifically designed microRNA (miR) (KD-Gpr88) in a 6-OHDA rat model of hemi-parkinsonism. Then, we investigated the effects of the KD-Gpr88 in the DA-deprived dorsal striatum on circling behavior and LID as well as on specific markers of striatal neuron activity. The KD-Gpr88 reduced the acute amphetamine-induced and increased L-DOPA-induced turning behavior. Moreover, it normalized the upregulated expression of striatal Gad67 and Proenkephalin provoked by the 6-OHDA lesion. Finally, despite promoting FosB accumulation, the KD-Gpr88 was associated neither with the upregulation of Prodynorphin, which is causally linked to the severity of LID, nor with the aggravation of LID following chronic L-DOPA treatment in 6-OHDA-lesioned rats. These results thus justify further evaluation of Gpr88 as a potentially novel target for the management of PD as an alternative to L-DOPA therapy.